Enriching Culinary Variety through Ice Cream Innovation with Traditional Herbal Medicine Turmeric Acid at Jinggo Café & Restaurant - Dwi Nur Hidayati, Shinta; Randhi Nanang Darmawan; Wiralatief Sanjaya, Aditya (P3M Politeknik Negeri Jember, 2024)
The development of Tourism encourages the development of health tourism (wellness tourism and herbal tourism) by re-socializing herbal medicine, by innovating the utilization of sour turmeric herbal medicine into sour turmeric herbal ice cream so that it becomes a culinary alternative. This study aims to determine the manufacturing process, the level of public liking and cost analysis. The type of approach used is research and development (R&D) with the 4D development model (Define, Design, Development and Dissemination) which uses hedonic and hedonic quality organoleptic tests. The results showed that the best recipe used a ratio of 40% herbal medicine: 100% milk with a favorability level of 86.7%. In the process of making sour turmeric herbal ice cream through several stages, namely preparation of ingredients, mixing ingredients, pasteurization, homogenization, aging or freezing, packaging and storage. With the selling price of the Sour Turmeric Herb Ice Cream product IDR 6,000 / portion.